Les Prétérits nord-occitans à consonne thématique /t - Louise Esher (Revue des Langues Romanes)
In a subgroup of northern Occitan varieties, the preterite is characterised by a thematic consonant /t/. This study draws on data from a range of published sources (linguistic atlases, dialect descriptions, historical grammars, literary texts) and from fieldwork, in order to establish the geographical range of such preterite forms, to analyse their paradigmatic distribution and to examine their historical development. Diachronic and comparative analyses show that the most plausible hypothesis put forward to explain the emergence of preterites with thematic /t/, is that of analogical remodelling based on the third person singular form, reanalysed as a bare stem and extended to the other person forms. The systematicity of the developments indicates that they reflect fundamental structural properties of the inflectional system.